Monitoring of waters status on the area of the waste landfill case study Piškornica - Nemčić-Jurec, Jasna (2019)
The remediation of the municipal waste landfill reduces the harmful effects of inadequately disposed waste in the environment and reduce the risks on human health. The aim of this paper is to evaluate the efficiency of the remediation (2005 to 2012) of waste landfill of Piškornica. Groundwater from piezometers (P2, P3, P4 and P5) at Piškornica and surface water from the Gliboki stream (upstream and downstream) were analyzed, before and after the remediation. The results of the analyzed parameters (KPK, BPK5, electroconductivity, iron) showed significant decrease in values (p <0.05) and up to 82% (BPK5 in P5) after remediation. The most significant decrease in the value of the indicators was determined in the P5, which is nearest and downstream from the landfill body. Significant difference (p <0.05) was not found at the upstream and downstream locations of the Gliboki stream basin before and after remediation. The numerical model of the groundwater flow shows that groundwater pollution will not occur even in the worst scenario (the largest possible pumping of 420 l/s) of the current capacity of the Ivanščak source. The results contributed to decisions on water management and further monitoring of water plans on landfill area.
Bibliografija: str. 57-58.
Summary.
Keywords: Odlagališta otpada -- Sanacija -- Podzemne vode -- Numerički modeli; Koprivnica